ANALYSIS OF NUMERATION ABILITY PROFILE OF ELEMENTARY SCHOOL STUDENTS BASED ON AKM COGNITIVE LEVEL: A DESCRIPTIVE META-ANALYSIS STUDY - Riduan Febriandi Febri; Zaenal Abidin; Laely Farokhah; Yeni Dwi Kurino (Jurnal Cakrawala Pendas, 2026)
This study aims to analyze the profile of elementary school students' numeracy abilities based on the cognitive levels of the Minimum Competency Assessment (AKM), namely knowing, applying, and reasoning, through a descriptive meta-analysis approach based on the Systematic Literature Review (SLR). Numeracy is an essential competency of the 21st century that is the foundation for developing logical, critical, and problem-solving thinking skills since elementary school. The national assessment policy through AKM requires Mathematics learning that is not only oriented towards mastery of concepts, but also reasoning and application in real-life contexts. This research method refers to the PRISMA 2020 guidelines by analyzing 30 scientific articles published between 2019 and 2025, consisting of articles from national journals accredited by SINTA 1–2 and international journals indexed by Scopus. Data were analyzed descriptively quantitatively by classifying numeracy indicators into AKM cognitive levels. The results showed that elementary school students' numeracy abilities were dominated by the knowing level, followed by applying, while the reasoning level was the lowest achievement. These findings indicate the need to strengthen numeracy learning based on reasoning and authentic contexts. This research provides important implications for teachers, researchers, and policy makers in improving the quality of elementary school mathematics learning in line with AKM demands.